THE EFFECT OF GLASS POWDER WASTE AS A SUBSTITUTE MATERIAL FOR BINDER ON THE VALUE OF COMPRESSIVE STRENGTH AT 28 DAYS AND FLOWABILITY IN SELF COMPACTING CONCRETE (SCC). - Wahyudin, Ade; Abdiantoro, Adji Putra (Universitas 17 Agustus 1945 Jakarta, 2024)
By using glass powder instead of cement, glass waste will become a new alternative for the construction industry and a solution to the problem of excess waste. Since glass is resistant to weather and chemical substances that resemble cement or can bond, glass waste can be used as a concrete filler. In this study, a quantitative method was used, with 12 samples having variations of 0%, 5%, 10%, and 15%. The variables measured were the compressive strength of concrete at 28 days of age and smoothness, while the controlled variable was the use of glass powder as a substitute for binder. In this study, variations of glass powder replacement of 0%, 5%, 10%, and 15% of the binder weight were used. The results showed that 0% (617mm)c, 5% (620mm), 10% (628mm) and 15% (644mm) had an influence on the slump flow of fresh concrete. The results of testing the compressive strength of 28-day-old concrete obtained consecutive results of 41.86 Mpa, 48.55 Mpa, 38.84 Mpa, and 35.64 Mpa. The results show that 5% replacement has a higher compressive strength. In addition, the use of glass powder as a substitute increases the flow velocity of SCC concrete proportionally with the percentage of replacement. However, other factors should be considered.